2018
DOI: 10.1111/jcmm.13688
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor ATF3 mediates the radioresistance of breast cancer

Abstract: This study was designed to research the influence of activating transcription factor 3 (ATF3) on the radioresistance of breast cancer. ATF3 expression was measured by qRT‐PCR and immunohistochemistry. Cancerous cell lines were cultured in vitro, and the expression of ATF3 was gauged by both qRT‐PCR and Western blot before and after the radiation therapy. Cellular cycle and apoptosis were analysed by flow cytometry. Changes in the expression of corresponding proteins in the downstream pathways were identified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…It was recently reported that PI3K/AKT inhibitor inhibited the resistance to endocrine or DNA‐damaging radiotherapy in ER‐positive early patients with BC 31 . Besides, activation of the AKT pathway might also contribute to the radioresistance in BC and glioblastoma cells 13,26 . Consistent with this notion, our data show that the viability was increased in cells treated with LY294002 and radiation than in cells treated with radiation alone in the absence or presence of CPNE1 overexpression, suggesting that CPNE1 regulates TNBC radiosensitivity by regulating AKT activation.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…It was recently reported that PI3K/AKT inhibitor inhibited the resistance to endocrine or DNA‐damaging radiotherapy in ER‐positive early patients with BC 31 . Besides, activation of the AKT pathway might also contribute to the radioresistance in BC and glioblastoma cells 13,26 . Consistent with this notion, our data show that the viability was increased in cells treated with LY294002 and radiation than in cells treated with radiation alone in the absence or presence of CPNE1 overexpression, suggesting that CPNE1 regulates TNBC radiosensitivity by regulating AKT activation.…”
Section: Discussionsupporting
confidence: 89%
“…31 Besides, activation of the AKT pathway might also contribute to the radioresistance in BC and glioblastoma cells. 13,26 Consistent with this notion, our data show that the viability was increased in cells treated with LY294002 and radiation than in cells treated with radiation alone in the absence or presence of CPNE1 overexpression, suggesting that CPNE1 regulates TNBC radiosensitivity by regulating AKT activation. However, whether DNA-damaging radiotherapy depends on the AKT signaling is still unknown.…”
Section: Mda-mb-231 Cells Demonstrated a Higher Survival Fraction Thansupporting
confidence: 81%
See 2 more Smart Citations
“…RIPK1 (Miyamoto, ) and TNFRS21 (Benschop et al ., ) are components of the TNF pathway, whereas DUSP8 (Keyse, ) and HRAS (Knobbe et al ., ) act on the RAS‐MAPK pathway. Alteration in the activity of transcription factors could be critical for the development and maintenance of radioresistance in breast cancer by control genes of the survival pathways, such as the RAS‐MAPK and TNF pathways (Ishihara et al ., ; Zhao et al ., ). Many of the genes that we observed to be down‐regulated in the transcriptome analysis might be part of an epigenetic network of transcriptional silencing driven by axis miR‐122‐ ZNF611 or miR‐122‐ ZNF304 .…”
Section: Discussionmentioning
confidence: 97%